Acceso a internet en la parroquia Boyacá del cantón Chone mediante radioenlace gestionado con tecnología Wireless Lan Controller - Ortiz Rodríguez, Quinto Emiliano (2019)
The purpose of this degree work is to develop a Wi-Fi wireless connection network model to obtain Internet access in the Boyacá parish - Chone canton through radio link managed with Wireless LAN Controller (WLC) technology that provides free internet access. The PPDIOO methodology (Prepare, Plan, Design, Implement, Operate and Optimize) was used for its execution process; using its first three phases. It began with the preparation stage where a structured survey with closed multiple-choice questions was developed, which allowed determining the need for the implementation of this project, as well as a study of the area for the identification of the technology to be used through Radio Mobile software. The planning continued, where the network requirements were identified, the equipment that would be used for this model, the quantity, the technology to be used and the connection that this network would have. Finally, the design, where the location of the equipment and the configuration of each of them is established. As a result of this proposal, a Network Design Plan for the implementation of managed radio link was obtained, which proposes the necessary guidelines to contribute to the reduction of the digital divide.